2006
DOI: 10.1097/01.ogx.0000234636.46704.ad
|View full text |Cite
|
Sign up to set email alerts
|

Caesarean Section on Request: A Comparison of Obstetricians??? Attitudes in Eight European Countries

Abstract: This study was a small-scale, "quasirandomized," controlled trial carried out to determine the effectiveness and safety of cervical cerclage performed using the McDonald technique in patients with symptomatic placenta previa. Outcomes were compared in 18 women undergoing cerclage and 19 control women. Criteria for admission to the study included painless vaginal bleeding, a gestational age of 20 to 34 weeks, and sonographic confirmation of the diagnosis. Gross congenital anomalies, other complications, type 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 0 publications
2
62
0
3
Order By: Relevance
“…Concerning reliability, Test-retest was not performed in this study as parts of the questionnaire had been used successfully in previous studies (Cuttini et al, 2006;Habiba et al, 2006). The questionnaire consisted of different parts.…”
Section: Methodological Considerationmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning reliability, Test-retest was not performed in this study as parts of the questionnaire had been used successfully in previous studies (Cuttini et al, 2006;Habiba et al, 2006). The questionnaire consisted of different parts.…”
Section: Methodological Considerationmentioning
confidence: 99%
“…Each responsible coordinator was required to ensure that this deadline was met. The midwives were recruited from the same Swedish units that participated in the EUROBS study: (Development of Perinatal Technology and Ethical Decision-making during Pregnancy and Birth; the attitudes of obstetricians from eight European countries) (Cuttini et al, 2006;Habiba et al, 2006). The heads of three units refused to give their consent, due either to reorganisation, a heavy workload or shortage of time.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obstetricians might take the mother's preferences into account when deciding on mode of delivery [26,27]. Previous research has shown that these preferences are determined to a large extent by mothers' level of education and their immigrant background [22,28,29]. Equation (1) was specified as a linear probability model, where the standard errors were clustered on hospital [30].…”
Section: Main Analysis -Empirical Specificationmentioning
confidence: 99%
“…The reasons for this increase are also matters of concern and are under analysis both from a medical and a public perspective since the "women's own choice" or cesarean on "maternal request" is thought to be the major reasons for the increase (1)(2)(3). Among the general public there is an agreement that women have the right to choose both on the basis of concern with bodily integrity and because of fear of childbirth (4).…”
Section: Introductionmentioning
confidence: 99%